KUFR DALAM PERSPEKTIF HADIS - Abidin, Zainal (Hunafa: Jurnal Studia Islamika, 2008)
Kufr is often considered an antithesis of imÃ¢n. In the mean time, imÃ¢n is the fundamental part of Islamic teaching. Nevertheless, as far as the sources of Islamic teaching are concerned, the term kufr cannotÂ  necessarily be graspedÂ  asÂ  disbelief in Allah (God). InÂ  someÂ  hadÃ®ths (the prophetâs traditions), we find some terms of kufr that do not indicate disbelief in AllÃ¢h at all. Even, some merely indicate disobedience of the Muslims in performing their Islamic teachings, such asÂ  Â performing salÃ¢t. Based on this, this article deals with kufrÂ  from the hadÃ®th perspective.Kata Kunci : kufr, perspektif hadis, dosa besar